Spore 193: Stemming youth migration - Opportunities in agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
The dossier explains how agriculture’s potential mitigates youth migration. This Spore issue also includes articles on blended finance funds and fair trade as well as an interview of Michael Hailu who emphasises the role of digitalisation as a game changer in agriculture.